Hypercalcemia induced with an arotinoid in thyroparathyroidectomized rats. New model to study bone resorption in vivo. - Trechsel, U (1987)
A model of stimulated bone resorption was developed using a synthetic retinoid in thyroparathyroidectomized rats. The retinoid induced an increase in bone resorption and in the number of vertebral subperiosteal osteoclasts. The resulting increase in plasma Ca could be used as an easily measured index of bone resorption. Three bisphosphonates produced a dose-related prevention and reversal of retinoid-induced hypercalcemia. Their potencies were similar to those previously obtained by histomorphometry. Irradiation (600 rad) of the rats prevented hypercalcemia but failed to reverse it, showing that proliferation of osteoclast precursor cells was important in inducing, but not in maintaining, bone resorption. Calcitonin produced similar effects on calcemia and prevented the increase in osteoclast number but failed to reverse the increase, suggesting that it inhibited precursor proliferation. This model represents a new tool to study mechanisms of bone resorption and the action of inhibitors in vivo.